(untitled) (Revista Apotheke, 2026)
The overall objective of this educational research in art is to create pedagogical spaces for encounter, experimentation, thought, and invention with artistic languages, particularly contemporary and traditional textiles. Since 2013, the Weaving Workshop located in the Bachelor’s Degree in Culture and Art at the University of Guanajuato, the institution where we work, has been characterized as a place that fosters experiences for doing, feeling, and thinking using threads and weaves. In this text, we seek to present some work processes and the methodological possibilities and reflective paths that we have observed/found in the teaching and artistic practice carried out with students who have taken the workshop. We investigate how working with artistic production processes, which involves the development of knowledge, skills, and competencies in art, has been reinterpreted by young university students in their personal and collective textile production projects.